2017
DOI: 10.1097/01.ogx.0000515080.87623.78
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Quantitation of Mitochondrial DNA Reveals Uniform Levels in Human Blastocysts Irrespective of Ploidy, Age, or Implantation Potential

Abstract: Main Outcome Measure(s): For each sample the mtDNA value was divided by the nuclear DNA (nDNA) value and the result was further subjected to mathematical analysis tailored to the genetic makeup of the source embryo.Result(s): On average the mathematical correction factor changed the conventionally determined mtDNA score of a given blastocyst via NGS by 1.43% +/-1.59% (N=1396), with maximal adjustments of 17.42%, and via qPCR by 1.33% +/-8.08% (N=150), with maximal adjustments of 50.00%. Levels of mtDNA in eupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 25 publications
(37 reference statements)
0
20
2
Order By: Relevance
“…These findings are supported by the observation that mitochondrial dysfunction is associated with mitochondrial hyperproliferation: the hypothesis is that an increase in mtDNA copy number in an early embryo could represent some metabolic stress (38). In contrast to these reports, a study based on the analysis of mtDNA content from 1,396 embryos showed no statistically significant differences in blastocysts grouped by ploidy, maternal age or implantation potential (39). The substantial innovation was the development of a mathematical formula taking into account the genomic variation deriving @ C I C E d i z i o n i I n t e r n a z i o n a l i from confounding factors, such as embryo gender and ploidy.…”
Section: Mitochondrial Dnacontrasting
confidence: 54%
“…These findings are supported by the observation that mitochondrial dysfunction is associated with mitochondrial hyperproliferation: the hypothesis is that an increase in mtDNA copy number in an early embryo could represent some metabolic stress (38). In contrast to these reports, a study based on the analysis of mtDNA content from 1,396 embryos showed no statistically significant differences in blastocysts grouped by ploidy, maternal age or implantation potential (39). The substantial innovation was the development of a mathematical formula taking into account the genomic variation deriving @ C I C E d i z i o n i I n t e r n a z i o n a l i from confounding factors, such as embryo gender and ploidy.…”
Section: Mitochondrial Dnacontrasting
confidence: 54%
“…Blastocysts derived from patients seeking infertility treatment were generated by in vitro fertilization and embryo culture as previously described (Victor et al, 2017), and were evaluated using the Gardner system (Gardner and Schoolcraft, 1999). As part of the embryo selection process, a clinical 5-10 cell TE biopsy was collected and blastocysts were vitrified.…”
Section: Embryos and Clinical Pgt-a Analysis By Ngsmentioning
confidence: 99%
“…According to the “quiet embryo” hypothesis, under ideal circumstances, embryos are in low metabolic activity, which suggests that a viable embryo has a relatively lower metabolism, whereas those under stress and of reduced developmental potential, tend to be metabolically more active (Ravichandran et al, ). Elevated mtDNA levels and by extension increased adenosine triphosphate (ATP) production could be a compensatory mechanism providing distressed embryos with more chemical energy to overcome adverse conditions (Victor et al, ). MtDNA replicates since the primordial germ cell stage and the MII oocyte fixes its mtDNA composition before fertilization (St. John, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the increased level of mtDNA observed in abnormal or inferior embryos might be a sign of dysplasia and this may be caused by a compensatory mechanism to an internal or external environment (Diez‐Juan et al, ). However, a group recently reported that the standardized calculation method of mitochondrial DNA does not have a predictive value, and that age, ploidy as well as implantation potential are not linked to mtDNA content at all (Victor et al, ). Treff et al () also demonstrated that mtDNA quantitation does not distinguish between implantable embryos and nonimplanted embryos after double embryo transfer in a single person.…”
Section: Introductionmentioning
confidence: 99%